EFFECT OF MUTRAMARGAGATA UTTARBASTI WITH ASHWAGANDHA TAIL IN MUTRAVAHA SROTODUSHTI W.S.R. TO STRESS INCONTINENCE- A CASE STUDY (AYUSHDHARA, 2020)
Woman, a pillar of strength is always like a lantern in night. Being a creator of life, female plays a wide range of roles in her entire lifespan. Woman’s health is an important aspect in progress & maintenance of wealth for her own family, society and ultimately nation. Woman is as delicate as flower. During different stages of life, she may suffer from various diseases and conditions that affect her physical and emotional well - being which in turn alter her quality of life. Stress incontinence is one of the gynaecological conditions mostly in reproductive as well as postmenopausal age group. It adversely affects physiological as well as psychological health of female & even interfers with the professional life. Most of women feel inconvenience specially in their day to day activities either due to frequent vulval pads they need to use or frequent changing of undergarments. So, it is major problem in front of women and ultimately gynaecologistsStress urinary incontinence is an involuntary escape of urine from the external urinary meatus due to sudden rise in Intra Abdominal Pressure. Women can’t have any natural control on it. Due to it, escape of urine while sneezing, coughing or laughing occurs. It is common condition affecting 25-40% of women. Conservative & surgical methods are available for its management. But due to some drawbacks we need to explore and use Ayurvedic treatments given in Samhitas.Ayurvedic texts has described Uttarbasti in detail. When it is given per urethra as indicated in texts, may help in curing certain diseases related to Apana Kshetra. Stress incontinence can be correlated with Alpalpa Mutrapravrutti in Mutravaha Srotodushti. So, attempt is made to cure stress incontinence with the help of Mutramargagata Uttarbasti.